2013
DOI: 10.1007/s11357-013-9531-1
|View full text |Cite
|
Sign up to set email alerts
|

The decline of verbal and visuospatial working memory across the adult life span

Abstract: It has been well established that working memory abilities decrease with advancing age; however, the specific time point in the adult life span at which this deficit begins and the rate at which it advances are still controversial. There is no agreement on whether working memory declines equally for visuospatial and verbal information, and the literature disagrees on how task difficulty may influence this decay. We addressed these questions in a lifespan sample of 1,500 participants between 21 and 80 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 62 publications
8
34
0
Order By: Relevance
“…Third, the finding that education has a positive linear association with WM abilities is consistent with previous studies of younger and older adults that have examined this issue. As we saw in the Introduction, previous studies have reported positive main effects of education across younger and older adults (Brockmole & Logie, 2013;Cansino et al, 2013;van Gerven et al, 2007), with one study finding positive effects in older but not younger adults (Dorbath et al, 2013). Additionally, Fournet and colleagues (2012) reported that education was positively associated with WM performance in their sample of older adults (aged 55-85).…”
Section: Interpretation Of Resultsmentioning
confidence: 84%
“…Third, the finding that education has a positive linear association with WM abilities is consistent with previous studies of younger and older adults that have examined this issue. As we saw in the Introduction, previous studies have reported positive main effects of education across younger and older adults (Brockmole & Logie, 2013;Cansino et al, 2013;van Gerven et al, 2007), with one study finding positive effects in older but not younger adults (Dorbath et al, 2013). Additionally, Fournet and colleagues (2012) reported that education was positively associated with WM performance in their sample of older adults (aged 55-85).…”
Section: Interpretation Of Resultsmentioning
confidence: 84%
“…There has been debate regarding the potential role of relatively active processing in age-related cognitive decline. Previous research has suggested that active tasks, which involve transforming, manipulating, or integrating information ( Cornoldi and Vecchi, 2003 ) are more sensitive to aging ( Vecchi and Cornoldi, 1999 ; Vecchi et al, 2005 ; Cansino et al, 2013 ). Indeed, in a meta-analysis, Bopp and Verhaeghen (2005) demonstrated progressively larger age-related deficits depending on the extent of active processing required in a task, from simple (forward) storage span, to backward span, and finally to processing intensive working memory tasks such as sentence span.…”
Section: Discussionmentioning
confidence: 99%
“…Declines in processing speed occur earlier in the lifespan compared with other cognitive domains (10) and are thought to be a result of relatively widespread reductions in white matter microstructure (13,16). Additionally, nonverbal working memory performance declines sharply with age (4,53) and is sensitive to age-related changes in prefrontal and temporal microstructure and CRF in older adults (8,31).…”
Section: Measurementsmentioning
confidence: 99%